Simulation Of Natural Gas Combustion Process Using Pressure Based Solver - Osama H. Ghazal (European Scientific Journal, ESJ, 2016)
The aim of this research is to simulate the combustion process for methane using different heat transfer models combined with various fuel injection techniques to better understand the combustion process and heat transfer process inside IC engine which reflect on the engine efficiency. The simulation has been carried out using Lotus Engineering software. This model solves the nonlinear momentum and continuity equations to satisfy the conservation of mass and the conservation of momentum laws. In this analysis a single cylinder four stroke SI engine has been simulated. The fuel used in the simulation is methane. Two fuel systems have been investigated port injection and direct injection. The Wiebe heat release curve has been used. Two widely used for SI engines heat transfer models presented in the simulation, Annand and Woschni. The intension in this paper is to study the effect of various fuel systems and heat transfer models on engine efficiency for different engine speeds. Moreover, the evaluation of the heat transfer models for natural gas SI engine will be tested. Brake power, mean effective pressure, specific fuel consumption, brake thermal efficiency, and heat transfer rate were calculated and discussed to show the effect of varying heat transfer models and fuel systems on engine efficiency.